New benzo[a]phenoxazinium chlorides with chlorinated terminals at 2- and 9-positions - Firmino, A. D. G. (2011)
The synthesis of novel benzo[a]phenoxazinium salts possessing one, two or three chlorinated terminals at their substituents in 2- and 9- positions of the polycyclic moiety was carried out. These compounds displayed fluorescence emission in ethanol and water at physiological pH between 643 and 665 nm.